Autoimmune Myocarditis Caused by Immune Checkpoint Inhibitors Treated With Antithymocyte Globulin. Issue 7 (September 2018) - Jain, Varun; Mohebtash, Mahsa; Rodrigo, Maria E.; Ruiz, George; Atkins, Michael B.; Barac, Ana
Abstract : The immune checkpoint inhibitors have brought about a paradigm shift in the treatment of many cancers and are being used as the first line therapy in increasing number of aggressive malignancies, including metastatic melanoma. Their adverse effects, mostly mediated by an uncontrolled overactivation of the immune system, may compromise the therapeutic benefit. Combination immune checkpoint therapies in particular, have higher therapeutic efficacy, but have also been associated with a higher incidence of severe immune-related adverse effects including autoimmune lymphocytic myocarditis. Recent clinical reports of this rare and life threatening condition indicated rapid progression of severe hemodynamic and electrical instability, with or without acute decompensated heart failure, reduced ejection fraction and shock, pointing to the need for early recognition, diagnosis and prompt management. Current guidelines for management of other immune-related adverse effects recommend high-dose glucocorticoids, with consideration of immunomodulators, such as infliximab in patients with severe colitis. However, knowledge about the treatment approaches in immune-related myocarditis remains extremely scarce. Here we report a case of severe, steroid refractory, lymphocytic myocarditis that occurred after the first cycle of combination immunotherapy with the programmed cell death protein-1 inhibitor, nivolumab, and the cytotoxic T-lymphocyte-associated protein 4 blocker, ipilimumab, for metastatic melanoma. We discuss treatment approaches including the role for transvenous pacemaker, advanced heart failure support, and interdisciplinary decision making.